Management Strategy in the Implementation of the Legal Documentation and Information Network System - Nurini, Sri Hesti; Suyuti, Nurmadhani Fitri; Mujahid, Mujahid (Journal La Bisecoman, 2024)
This study aims to analyze management strategies in the implementation of the Legal Documentation and Information Network (JDIH) System at the Regional Secretariat of Penajam Paser Utara Regency. JDIH plays a crucial role in providing accurate, transparent, and easily accessible legal information for the public and local government. However, its implementation faces various challenges, such as limited socialization, inadequate technological infrastructure, and low public legal literacy. This study employs a qualitative approach. Data were collected through in-depth interviews, observations, and documentation. The results indicate that the main obstacles include the public's lack of understanding of JDIH, insufficient technological infrastructure, and difficulties in data synchronization across agencies. Based on the findings, this study provides recommendations to enhance human resource training, update technological infrastructure, and expand JDIH socialization. With effective management strategies, it is expected that the quality of legal information services in Penajam Paser Utara Regency can be improved, supporting transparency and openness of legal information.